Tracking pollutants in selected Brazilian drainages from araxá city - Bonotto, Daniel Marcos [UNESP] (Elsevier, 2020)
Sediments geochemical data from Araxá city, Minas Gerais State, Brazil, have provided new insights on the pollutants inputs in different drainage systems of Araxá city, Minas Gerais State, Brazil. The sediments profiles (6) provided from a lake (Grand Hotel) and streams (Sal, Areia, Fundo, and Feio). The local municipality uses some waters (Areia, Fundo, and Feio streams) in water-supply systems. Because of the Brazilian environmental agency does not establish concentration guidelines for several heavy metals occurring in freshwater sediments, the values reported in this paper were compared with limits proposed elsewhere. Enrichment Factor (EF) values of 20–40 (very high enrichment) and EF > 40 (extremely high enrichment) were found for Ba (in two sediment core), Nb (in three sediment core) and Se (in four sediment core). The 210Pb chronological method was useful for tracking some major events that occurred in the history of Araxá city, showing concentration peaks around 1962 and 1993 for BaO, Nb2O5, Fe2O3, P2O5, SO3, SrO and CeO2 and around 1972 and 1999 for SeO2.
Keywords: 210Pb chronological method; Araxá city; Barreiro alkaline complex; Brazil; Enrichment factor; Sediment core; Sediments geochemistry